Investigation into Shaped Wide-Beam Reflectarray Surfaces Reflectors as Passive Repeaters in Wireless Networks - Callaghan, Peter; Young, Paul R. (Journal of Electronics and Electrical Engineering, 2025)
This paper investigates the application of a reflectarray surface (RAS) for generating a shaped beam to serve as a passive repeater in wireless networks. A shaped beam can be desirable as it may provide coverage over a dead-spot region. Examples of a flat-topped and sloping top shaped beams having a nominal beamwidth of 30° and a steering angle of 40° at 10 GHz are investigated, designed using the particle swarm optimizer in MATLAB. Measurement and simulation from CST show reasonable agreement to the ’array factor’ synthesis patterns but display practical detuning effects that may limit this approach. Additionally, it was noted element factor has a more significant impact on such beam shaping.